Approaches to quality control, preclinical and clinical studies of live recombinant viral vector vaccines - L. M. Khantimirova; D. V. Gorenkov; S. G. Guseva; V. A. Merkulov; A. A. Soldatov (Биопрепараты: Профилактика, диагностика, лечение, 2021)
At present, there are not much data on the clinical use of live recombinant viral vector vaccines. Characteristics of new vaccines should be factored into requirements/recommendations for quality control, preclinical and clinical studies of vaccines in order to enable further risk/benefit assessment. The aim of this study was to analyse current approaches to quality control, preclinical and clinical studies of live recombinant viral vector vaccines. The paper provides an overview of the licensed live viral vector vaccines and those at various stages of clinical trials. The authors analysed Russian, European, American, and Japanese guidelines related to quality issues, preclinical and clinical studies of live viral vector vaccines. The analysis demonstrated that the regulatory requirements for live recombinant viral vector vaccines include assessment of a detailed rationale for vaccine development, including information on the choice of the vector, the origin of the heterologous antigen gene(s), elements related to the transgene(s) expression, as well as assessment of the genetic and phenotypic stability of the recombinant virus, the risk of reversion to virulence or recombination with wild type strains, the potential for virus genome integration into the host cell chromosome, the pre-existing immunity to the vector, the intensity of the immune response elicited by the vector, and the reusability of the vector. The choice and number of applicable toxicological and pharmacological models will depend on these aspects. The results of the analysis of approaches to quality control, preclinical and clinical studies of live recombinant viral vector vaccines may be used in the development of Russian regulatory guidelines harmonised with the international norms and regulations.